2014
DOI: 10.1016/j.egypro.2014.11.1082
|View full text |Cite
|
Sign up to set email alerts
|

Computational Fluid Dynamics Simulation of the Effect of Guide-vane Angles on the Performance of the Exhaust Air Energy Recovery Turbine Generator

Abstract: An exhaust air energy recovery turbine generator is designed to recover part of the energy in the discharged air from an exhaust air system. The design is a combination of H-rotor vertical axis wind turbines (installed in cross-wind position), guide-vanes and a diffuser. Its working principle was tested on a scaled model of cooling tower and simulated in a computational fluid dynamic (CFD) package. From the guide-vanes study, optimum guide-vanes arrangement is 100°, 70° and 90°. The system with optimized guide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…8. Torque coefficient for the system without diffuser and guide-vanes, and the system with diffuser and guide-vanes at optimized angles [58] Then, with the presence of the VAWT, a minor difference in power consumption by the fan motor was discovered in a research by Chong et al, [51], which was 0.39% higher. It showed that, there is no significant difference in air intake speed or current consumption of the power-driven fan was observed when the turbine rotated above the cooling tower in laboratory test and the outlet air speed of an actual induced-draft cooling tower showed no substantial variations in a field test.…”
Section: Exhaust Air Energy Recovery Power Performancementioning
confidence: 98%
See 3 more Smart Citations
“…8. Torque coefficient for the system without diffuser and guide-vanes, and the system with diffuser and guide-vanes at optimized angles [58] Then, with the presence of the VAWT, a minor difference in power consumption by the fan motor was discovered in a research by Chong et al, [51], which was 0.39% higher. It showed that, there is no significant difference in air intake speed or current consumption of the power-driven fan was observed when the turbine rotated above the cooling tower in laboratory test and the outlet air speed of an actual induced-draft cooling tower showed no substantial variations in a field test.…”
Section: Exhaust Air Energy Recovery Power Performancementioning
confidence: 98%
“…Henceforward, to absorb the more wind energy from the exhaust air system, two VAWTs are combined with the enclosure (which includes multiple guidance valves and two diffuser plates). Multiple air flow channels are formed between the exhaust outlet and the VAWTs by guide valves, which direct the exhaust wind in the most efficient direction on the turbine blade [56][57][58][59][60][61]. Nonetheless, a hybrid, non-destructive assessment approach is proposed to investigate the dynamic behaviour and reliability of this new design, which examines the possible causes of high vibration and corrects the vibration issue [62].…”
Section: Exhaust Air Energy Wind Turbine Configurationsmentioning
confidence: 99%
See 2 more Smart Citations